Screening pre-bariatric surgery patients for esophageal disease with esophageal capsule endoscopy - Shah, Ashish (Baishideng Publishing Group Co., Limited, 2013)
AIM: To determine if esophageal capsule endoscopy (ECE) is an adequate diagnostic alternative to esophagogastroduodenoscopy (EGD) in pre-bariatric surgery patients. METHODS: We conducted a prospective pilot study to assess the diagnostic accuracy of ECE (PillCam ESO2, Given Imaging) vs conventional EGD in pre-bariatric surgery patients. Patients who were scheduled for bariatric surgery and referred for pre-operative EGD were prospectively enrolled. All patients underwent ECE followed by standard EGD. Two experienced gastroenterologists blinded to the patient’s history and the findings of the EGD reviewed the ECE and documented their findings. The gold standard was the findings on EGD. RESULTS: Ten patients with an average body mass index of 50 kg/m(2) were enrolled and completed the study. ECE identified 11 of 14 (79%) positive esophageal/gastroesophageal junction (GEJ) findings and 14 of 17 (82%) combined esophageal and gastric findings identified on EGD. Fisher’s exact test was used to compare the findings and no significant difference was found between ECE and EGD (P = 0.64 for esophageal/GEJ and P = 0.66 for combined esophageal and gastric findings respectively). Of the positive esophageal/GEJ findings, ECE failed to identify the following: hiatal hernia in two patients, mild esophagitis in two patients, and mild Schatzki ring in two patients. ECE was able to identify the entire esophagus in 100%, gastric cardia in 0%, gastric body in 100%, gastric antrum in 70%, pylorus in 60%, and duodenum in 0%. CONCLUSION: There were no significant differences in the likelihood of identifying a positive finding using ECE compared with EGD in preoperative evaluation of bariatric patients.